2011
DOI: 10.1177/0954407011411377
|View full text |Cite
|
Sign up to set email alerts
|

Surface flow and wake characteristics of automotive external rear-view mirror

Abstract: To observe surface flow and wake structure around an automotive external rear-view mirror, the pressure distribution over the mirror skin and the velocity vector fields in the cross-sectional planes were measured using a pressure scanning system and hot-wire anemometry in a blow-down wind tunnel. Surface flow visualization was also used to investigate boundary layer flow over the mirror surface. It was found that the pressure coefficient became negative over the whole of the surface area, with the exception of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The mock-up system consisted of three flat screens that offer rear view mirror functionality. Kim et al [10] studied the surface flow and wake structure around an automotive external rear-view mirror and demonstrated that visualizations over the mirror housing surface and the driver side vehicle skin.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The mock-up system consisted of three flat screens that offer rear view mirror functionality. Kim et al [10] studied the surface flow and wake structure around an automotive external rear-view mirror and demonstrated that visualizations over the mirror housing surface and the driver side vehicle skin.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The mock-up system consisted of three flat screens that offered rear-view mirror functionality. Kim et al [18] studied the surface flow and wake structure around an automotive external rear-view mirror and demonstrated the visualizations over the mirror housing surface and the driver side vehicle skin. The computer-based simulation method is also used to detect and warn of objects present within the blind spots of automobiles [1].…”
Section: Review On Optimization Of Design Parameters Of Rear-view Mirrormentioning
confidence: 99%
“…m (Alternatives); j = 1, 2 … n (Criteria). Then the absolute difference (∆ i (j)) between the normalized cell value and the corresponding referential series value was determined by using equation (18).…”
Section: Grey Relational Analysis (Gra)mentioning
confidence: 99%